ANTIOXIDANT ACTIVITY, NUTRITIONAL COMPOSITION AND SENSORY EVALUATION OF MILLETS, LEGUME AND MARJORAM (Origanum majorana L.) LEAF-BASED BISCUITS (Applied Biological Research, 2023)
This study was carried out to evaluate the effects of varying proportions of  some flour mixtures on sensory properties of biscuits; and the most acceptable types of biscuits were assessed for their nutritional properties.  Based on organoleptic evaluation, it was found that the biscuits developed  from blanched pearl millet: sorghum: germinated mung bean in ratio of  40:30:30 (Type III) and with marjoram or Marwa (Origanum majorana L.) leaf powder. Type VI (in ratio of 35:30:30:5) composite flours were the most  acceptable products. Nutritional evaluation of value-added biscuits revealed that Type-III biscuits had higher moisture (11.56%) and crude protein  (11.56%), while crude fibre (3.89%) and ash (1.08%) contents were higher  in Type-VI biscuits. Dietary fibre and mineral contents were maximum in Type-VI biscuits. Type-IIIavailability of calcium (59.69%). Phytic acid and polyphenol contents were  higher in Type III biscuits. The antioxidant activity was maximum in Type VI biscuits.
Keywords: Antioxidant content; biscuits; marjoram; nutritional composition; sensory evaluation